European ICT poles of excellence: The geography of European ICT activity and its policy implications - Daniel Nepelski; Giuditta De Prato (Intereconomics, 2014)
The European Commission is trying to increase the EU's competitiveness by building on its assets, particularly its many ICT industrial clusters. The Commission is seeking to strengthen the role of European ICT poles of excellence (EIPEs). But where are EIPEs and what are their characteristics? This paper reports the results of a project that casts more light on the geography of European ICT activity and indicates the key ICT locations in Europe. The project results show that excellence is scarce and is built on solid foundations in science and technology and industrial activity. We discuss the challenges to the EU's ambition to nurture five additional EIPEs within the next few years and present policies which could strengthen the position of existing EIPEs and improve the performance of potential candidates so that they play a stronger role in European ICT activity.
Keywords: 330; IKT-Sektor; Internationaler Wettbewerb; IKT-Politik; Standortfaktor; EU-Wirtschaftspolitik; Regionales Cluster; EU-Staaten